Need for inclusion of social determinants and effective mental health approach. A critical look at the Peruvian telework legislation - Gonzales Chinchay, Danny Javier (2023)
Telework has reconfigured labor relations in organizations and made more visible the mental health problems that affect workers. The intensive use of new information and communication technologies, the overload of work, the extension of working hours, and the blurring of boundaries between the world of work and the family, among other typical factors of teleworking, are significantly affecting mental health. Mental disorders such as workrelated stress, depression, anxiety, and exhaustion are becoming more common. This new scenario has generated a legal response. In our country, the Telework Law, and its Regulations, among other rules, provide important but insufficient and limited legal treatment on the subject. Therefore, it is imperative that new legal tools are developed so that the operators of the law are better qualified to settle disputes relating to the protection of workers’ rights to mental health. In this sense, taking into consideration the social determinants and, in particular, the psychosocial risk factors, this article aims to promote the creation of a special legal regulation on the protection of the right to mental health of teleworkers, especially when we are facing a right of enhanced protection.